(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Three different clay mineral assemblages are detected in mud-sandy bottom sediments of the Paraná Basin of Argentina. A dominant Kaolinite association, with sources areas in the Upper Amazon, north-east of the study area and within the Brazilian Shield (also with subordinated crystalline Illite); an Illitic- Smectitic and Interlayer I/S association, from the Andean Cordillera and the Chaco Plains in the north-west and mainly represented by the Bermejo and Pilcomayo Rivers; a southern Illitic-Chlorite dominant, but with lower crystallinity index than in the northern area, whose source is in the Pampean Plains to the west of Argentina. Mixed layer clays (Illite/Smectite) were also detected in this southern sector. These clay mineral associations reflect not only the climate but the source rock composition in these three main geographical areas. The tributaries of the lower Paraná River Basin show a dominant Illitic-Smectitic clay mineral association that has been eroded and transported from the Pampean Plains. In this contribution, three main clay mineral associations (Illite-Chlorite, Smectite-I/S, and Kaolinite) in stream sediments of the Paraná River and tributaries within a wide area of Argentina are described and their provenance is interpreted on the basis of controlling factors, climate and provenance.